Analysis of square shaped Microstructure based Electron Beam induced deposition - Siti Fatimah Abd. Rahman (Universiti Malaysia Perlis, 2008)
The fabrication of square shaped microstructures is studied by electron beam induced deposition (EBID) method using Scanning Electron Microscopy (SEM). EBID is a technique that allows the resistless deposition directly onto the sample substrate. Without using the precursor gas, the square shaped structures are grown in varies of deposition time. The deposition time was controlled from 6 ~ 18 minutes respectively with fixed beam energy 20 kV. In addition, the size, thickness and surface roughness of square shaped structures is studied by using atomic force microscopy (AFM). Increasing the deposition time from 6 ~ 18 minutes will increase the structures thickness from 38.16 nm to 92.08 nm while the rms value for surface roughness will decrease from 2.73 nm to 1.31 nm.